100% All Natural Ambiguity: A Comparative Approach to Food Labeling Requirements for the Term “Natural” By the Food and Drug Administration and the European Union - Andréa Maehara (Washington University Global Studies Law Review, 2019)
Despite being the only regulatory agency empowered to establish definitions for food product labeling, the Food and Drug Administration (FDA) has not formally defined the term “natural.” The FDA’s reluctance to fully define the term increases consumer distrustful of the FDA as a regulatory body and has also led to a dramatic increase in class action lawsuits against major food corporations. This Note will argue that the FDA should issue a formal definition in order to standardize usage of “natural” on food labeling by incorporating the European Union (EU)’s approach. First, this Note will examine the origins of the term “natural” by comparing the different approaches to the food labeling requirements in the United States through the FDA and in the European Union. Next, it will analyze the FDA’s current regulations and argue that these measures are too generic to guide food manufacturers and protect consumers. Finally, this Note will provide suggestions for the formal definition based on the approaches taken by the EU and its member states. Ultimately, if the FDA continues to resist implementing a formal definition for “natural,” there will be continue to be increases in class action lawsuits from frustrated consumers without federal preemption results as well as growing distrust of both the FDA and American food manufacturers.
Keywords: food; drug; fda; natural; labeling; europe; european union